the adventures of tom sawyer: philippine edition - Twain, Mark; Mark Twain (philippines Heinle cengage learning, 2010)
The Adventures of Tom Sawyer (1876) by Mark Twain is a classic coming-of-age novel following a mischievous boy, Tom, and his adventures in a small Mississippi town. Tom falls for Becky Thatcher, navigates school, and witnesses a murder by Injun Joe with his friend Huckleberry Finn, ultimately becoming a local hero.
English